A Comparative Analysis of Linear and Nonlinear Control of Wave Energy Converter for a Force Control Application. (2019) - Parwal, A.; Fregelius, M.; Almeida, P.M.; Svensson, O.; Temiz, I.; Oliveira, J. G.; Boström, C.; ,; Leijon, M.
No abstract available